Study on External Gas-Assisted Mold Temperature Control for Improving the Melt Flow Length of Thin Rib Products in the Injection Molding Process - Phan The Nhan; Thanh Trung Do; Tran Anh Son; Pham Son Minh (Advances in Polymer Technology)
In the injection molding process, mold temperature control is one of the most efficient methods for improving product quality. In this research, an external gas-assisted mold temperature control (Ex-GMTC) with gas temperature variation from 200°C to 400°C was applied to thin wall injection molding at melt thicknesses from 0.2 to 0.6 mm. The melt flow length was evaluated through the application of this system to the mold of a thin rib product. The results show that the heating process achieves high efficiency in the initial 20 s, with a maximum heating rate of 6.4°C/s. In this case, the mold surface reached 158.4°C. By applying Ex-GMTC to a 0.2 mm flow thickness, the flow length increased from 37.85 to 41.32 mm with polypropylene (PP) material and from 14.54 to 15.8 mm with acrylonitrile butadiene styrene (ABS) material. With the thin rib mold and use of Ex-GMTC, the mold temperature varied from 112.0°C to 140.8°C and the thin rib height reached 7.0 mm.